Return of spontaneous circulation (ROSC) dengan menggunakan resusitasi jantung paru (RJP) mekanik dan manual: A literature review - Nugroho, Joko (Holistik Jurnal Kesehatan, 2024)
Background: Cardiac arrest is a condition where a person's heartbeat stops suddenly due to damage to the heart's electrical system so that the heart cannot circulate blood throughout the body. If this is not treated immediately it can cause more severe brain damage. Of the 58 million people in the world, 31% of deaths are caused by heart disease. It is estimated that around 17.8 million deaths each year are caused by cardiovascular disease and of the total deaths in 1 year around 31% worldwide.Purpose: To provide an overview of the results of a literature review regarding the effectiveness of using mechanical compression and manual compression in cardiac arrest patients.Method: This research uses a literature review method, namely a method of selecting literature from various sources and then analyzing the literature to obtain a conclusion. The journals taken in conducting this literature review are journals that discuss topics with four types of keywords, namely effectiveness, manual resuscitation, mechanical resuscitation, and return of spontaneous circulation (ROSC).Results: Based on searches and reviews of 10 journals, it was found that mechanical compression was more effective than manual. Mechanical compression has not only been proven to help ROSC in cardiac arrest patients but the use of mechanical devices does not cause higher traumatic injuries when compared with manual compression.Conclusion: Mechanical devices do not cause a higher rate of traumatic injury when compared with manual compression. Keywords: Effectiveness; Manual Resuscitation; Mechanical Resuscitation; Return of Spontaneous Circulation (ROSC). Pendahuluan: Keadaan henti jantung (cardiac arrest) merupakan keadaan terhentinya detak jantung yang secara tiba-tiba terjadi pada seseorang disebabkan oleh kerusakan sistem kelistrikan jantung sehingga jantung tidak dapat memberikan aliran darah ke seluruh tubuh. Bila hal ini tidak segera ditangani maka dapat menyebabkan kerusakan otak yang lebih parah. Sebanyak 58 juta jiwa yang ada di dunia, 31% angka kematian disebabkan oleh penyakit jantung. Diperkirakan sekitar 17.8 juta kematian setiap tahunnya disebabkan dari penyakit kardiovaskuler dan dari total kematian dalam 1 tahun sekitar 31% di seluruh dunia.Tujuan: Untuk memberikan gambaran hasil   literature review tentang keefektifan penggunaan kompresi mekanik dan kompresi manual pada pasien henti jantung.Metode: Penelitian ini menggunakan metode literature review yaitu suatu metode memilih literatur dari berbagai sumber kemudian menganalisis literatur tersebut sehingga diperoleh sebuah kesimpulan. Jurnal yang diambil dalam pelaksanaan literature review ini adalah jurnal yang membahas mengenai topik dengan empat jenis kata   kunci yaitu, efektivitas, resusitasi manual, resusitasi mekanis, dan return of spontaneous circulation (ROSC).Hasil: Berdasarkan penelusuran dan review 10 jurnal didapatkan kompresi mekanik lebih efektif dibandingkan dengan manual. Kompresi mekanik tidak hanya terbukti membantu ROSC pada pasien henti jantung namun penggunaan perangkat mekanis tidak menyebabkan cedera traumatis lebih tinggi bila dibandingkan dengan kompresi manual.Simpulan: Perangkat mekanis tidak menyebabkan cedera traumatis lebih tinggi bila dibandingkan dengan kompresi manual. Kata kunci : Efektivitas; Resusitasi Manual; Resusitasi Mekanis; Return of Spontaneous Circulation (ROSC).